Special trends in CBF and DREB2 groups in Eucalyptus gunnii vs Eucalyptus grandis suggest that CBF are master players in the trade‐off between growth and stress resistance. Issue 4 (12th January 2017) - Nguyen, Hong C.; Cao, Phi B.; San Clemente, Hélène; Ployet, Raphaël; Mounet, Fabien; Ladouce, Nathalie; Harvengt, Luc; Marque, Christiane; Teulieres, Chantal
Abstract : Annotation of the Eucalyptus grandis genome showed a large amplification of the dehydration‐responsive element binding 1/C‐repeat binding factor ( DREB1/CBF ) group without recent DREB2 gene duplication compared with other plant species. The present annotation of the CBF and DREB2 genes from a draft of the Eucalyptus gunnii genome sequence reveals at least one additional CBF copy in the E. gunnii genome compared with E. grandis, suggesting that this group is still evolving, unlike the DREB2 group. This study aims to investigate the redundancy/neo‐ or sub‐functionalization of the duplicates and the relative involvement of the two groups in abiotic stress responses in both E. grandis and E. gunnii (lower growth but higher cold resistance). A comprehensive transcriptional analysis using high‐throughput quantitative real‐time polymerase chain reaction (qRT‐PCR) was performed on leaves, stems and roots from the two Eucalyptus species after cold, heat or drought treatment. A large CBF cluster accounted for most of the cold response in all the organs, whereas heat and drought responses mainly involved a small CBF cluster and the DREB2 genes. In addition, CBF putative target genes, known to be involved in plant tolerance and development, were found to be cold‐regulated. The higher transcript amounts of both the CBF and target genes in the cold tolerant E. gunnii contrasted with the higher CBF induction rates in the fast growing E. grandis. Altogether, the present results, in agreement with previous data about Eucalyptus transgenic lines over‐expressing CBF, suggest that these factors, which promote both stress protection and growth limitation, participate in the trade‐off between growth and resistance in this woody species.